Conflicts of Interest in Inflammatory Bowel Disease Articles on UpToDate. Issue 1 (11th October 2019) - Khan, Rishad; Li, Juana; Scaffidi, Michael A; Gimpaya, Nikko; Pivetta, Bianca; Grover, Samir C
Abstract: Background: Financial conflicts of interest (FCOIs) are widespread in inflammatory bowel disease (IBD) and may be particularly important in point-of-care (POC) resources, such as UpToDate, that are used to aid clinical decision making. In this study, we determined the prevalence of industry payments from companies making biologic medications for IBD to contributors of UpToDate articles on IBD. Methods: This cross-sectional analysis included UpToDate articles that mention the use of biologic medications for IBD. We collected the names of the contributors (authors and editors) and their disclosures on UpToDate. We then searched for their names on the Center for Medicare and Medicaid Open Payments database and compared the payment information from 2013 to 2018 with UpToDate's disclosures. We presented data per episode, which describes one instance of participation by one person in one article, regardless of whether that person contributed to multiple articles. Results: We identified 23 articles on the treatment of Crohn's disease and ulcerative colitis that mentioned the use of biologic medications, with 86 total episodes. Sixty-two (72%) episodes involved FCOIs. The median payment associated with each episode was $$55 (interquartile range = $44 to $145, 241). Contributors did not fully disclose FCOIs in 41 (48%) episodes. Deputy editors, who are required to be free of FCOIs, in general did not have substantial episodes involving FCOI. Conclusions: We found that UpToDate articles on inflammatory bowel disease involve substantial FCOI, many of which are not disclosed. The presence of these FCOIs may hamper trust in the objectivity of treatment recommendations.